SULFUR AND CARBON ISOTOPES IN THE BLACK SMOKER HYDROTHERMAL VENT ECOSYSTEMS OF THE URAL PALEOOCEAN - Lein A.Yu.; Ul'yanova N.V.; Maslennikov V.V.; Maslennikova S.P.; Zaikov V.V.; Spiro B. (My University, 2004)
The isotopic compositions of sulfide minerals and organic carbon (Corg) from the biomorphic ore of black smokers in the South Ural paleocean were studied. The δ34S values of sulfide minerals from pseudomorphs after vestimentiferas, mollusks, and polychaetas vary from -3.5 to +3.5‰. These, values characterize the sulfur isotopic composition of hydrogen sulfide from hydrothermal solutions in the Devonian ocean and testify to the catastrophic burial of the ancient bioherms studied, which retained the pseudomorphous ore texture and prevented their posthydrothermal alteration. The organic carbon of sulfidized organisms from ancient hydrothermal biological communities is enriched in 13C by 2-10‰ relative to the Corg of pre-Carboniferous sedimentary rocks. This supports the presence of chemoautotrophic organic matter in the biomorphic sulfide ore studied. It was demonstrated that kerite and kerite-like segregations typical of South Ural ore were produced by the metamorphism of biomass of ancient microbial mats.